Canopy arthropod faunas in fragmented agricultural landscapes - Majer, Jonathan; Keals, Natalie; Recher, H. F. (1999)
In late 1993 we initiated a study in the Western Australian wheatbelt and on the Northern Tablelands of New South Wales into the effect of habitat fragmentation on canopy arthropods. The Western Australian component of the study was performed at three locations; Amery, Namalcatching and Wyalkatchem Nature Reserves and nearby farmland. Two locations in the Armidale district were sampled In New South Wales; the Newholme Field Laboratory of the University of New England plus adjoining farmland north of Armidale, and private property at Thalgarrah north-east of Armidale. At each location, ten trees in each of four "growing situations", remnant centre, remnant edge, paddock and corridor, were selected for sampling. Arthropods were sampled from the upper canopyof wandoo Eucalyptus wandoo trees in Western Australia and Yellow Box E. melliodora trees in New South Wales by branchlet shaking. Nutrients were measured in associated foliage and soil beneath the sampled trees.Invertebrates were initially sorted to the "ordinal" level and compared between growing situations. There appears to be a fragmentation effect on canopy arthropod communities with significant differences in abundance and ordinal composition between remnant centres, edges, corridors and paddock trees. This may result from a balance between the positive influence of nutrient enrichment plus enhanced productivity at edges and in paddocks and the negative effects of tree isolation in paddocks and corridors. The effect of the former factors may outweigh the effect of the latter in paddocks, but not in corridors, where nutrient enrichment of foliage is not so high. Only certain species may respond to these differences, an effect that is masked in ordinal analyses; we will address this in future papers detailing the species responses of Homoptera, Hetaroptara, Thysanoptera and Coleoptera.